Profesionalisme Guru di Era Digital: Menjaga Integritas di Tengah Krisis Etika Pendidikan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The development of digital technology has brought significant changes to the world of education, including the roles and responsibilities of teachers as professional educators. In the digital era, teachers are required not only to master educational technology but also to uphold integrity and professional ethics amidst the rapid flow of information and shifting social values. This study aims to analyze how teachers can maintain professionalism and integrity amidst the ethical crises in education that arise from the unwise use of technology. The research employs a qualitative approach with a descriptive library research design. Data were obtained from various literature sources, including books, scholarly journals, and educational policy documents relevant to teacher professionalism and ethics. The findings indicate a gap between the idealism of teacher professionalism (das sollen) and the actual practice in the field (das sein), particularly in the application of digital ethics. Teacher professionalism in the digital era should not merely focus on technological competence but must also be grounded in moral values, responsibility, and exemplary conduct.